Pendampingan Usaha Melalui Pengadaan Sistem Pembayaran Digital (QRIS) dan Pembaharuan Banner Pada Loket Pembayaran BUMDes di Desa Sebuntal - Mariyah; Abner Owen Johannes Sianipar; Aisyah Insani Romadloni (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M), Universitas Mulawarman, 2025)
Micro, Small, and Medium Enterprises (MSMEs) and Badan Usaha Milik Desa (BUMdes) are the drivers of the economy in Sebuntal, Marangkayu sub district, Kutai Karatnegara Regency. The payment system is still manual and the the limited use of non-cash payment applications and banners do not yet contain BUMDes services encourage the implementation of community service. The activities conducted by assitance in making Quick Response Code Indonesia Standard (QRIS) and updating the BUMDes banners. The results of activities were indicated that Thai Tea 72 and BUMDes Sebuntal Berkah have QRIS barcodes for the payment system and updated banners at BUMDes payment counters. QRIS barcodes for the payment system is also made in acrylic stand. Financial services for payment systems are carried out more quickly and are supported by business actors whose competence is increasing and they are getting used to using non-cash transaction.